2016
DOI: 10.1016/j.watres.2016.04.065
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of hybrid adsorption/membrane pretreatment for low pressure membrane

Abstract: Fouling by natural organic matter (NOM) is a major obstacle when water from natural sources is treated using low-pressure membranes. Prior research by our group has demonstrated that passing natural water through a thin, pre-deposited layer of heated aluminum oxide particles (HAOPs) can remove substantial amounts of NOM from the feed and thereby reduce the fouling rate of downstream membranes. The work reported here explored the technical efficacy of such a pretreatment process under more challenging (and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
16
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 32 publications
5
16
1
1
Order By: Relevance
“…Presented results confirm existing reports that passage of feed through a thin layer of pre-coated HAOPs removes NOM and membrane foulants and substantially removes the majority of the UV254 from the raw water KIM et al 2007;2010;LIU 2016;MALCZEWSKA 2016;MALCZEWSKA, BENJAMIN 2016;MALCZEWSKA et al 2015].…”
Section: Resultssupporting
confidence: 89%
“…Presented results confirm existing reports that passage of feed through a thin layer of pre-coated HAOPs removes NOM and membrane foulants and substantially removes the majority of the UV254 from the raw water KIM et al 2007;2010;LIU 2016;MALCZEWSKA 2016;MALCZEWSKA, BENJAMIN 2016;MALCZEWSKA et al 2015].…”
Section: Resultssupporting
confidence: 89%
“…Early research on HAOPs documented reductions in membrane fouling and THM formation potential by pre-deposited HAOPs [10]. Subsequent work showed that, if raw water is filtered through a thin, pre-deposited layer of HAOPs upstream of a membrane, substantial amounts of NOM can be removed from the water, thereby reducing the fouling rate of downstream membrane units [11,12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Often pretreatment methods are used as preventative measures for controlling membrane fouling. These include the use of prefilters, screens, precipitation, coagulation, flocculation, or chemicals to reduce the amount of foulants in the feed [30][31][32][33]. In addition, membrane surface modification may be performed to lower the affinity of foulants for the membrane surface [30,[34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%